AN ANAYSIS OF PSYCHOLOGICAL CONFLICTS IN KHALLED HUSSAINI’S NOVEL THE KITE RUNNER - Toni Ibnul Fathi; Nur Ahmadi (Indonesian Journal of Social Sciences and Humanities, 2020)
This research is aimed at getting the description of psychological conflicts analysis of the main character in Khalled Hussaini’s Novel The Kite Runner. The problem statement of this research is formulated as follows; 1) The psycho logical conflicts experienced by main character in The Kite Runner novel, 2) how psychoanalysis is applied and 3) the motives of the main character in The Kite Runner novel. In this research, the writer uses descriptive qualitative and applies psychology theory and psychoanalysis approach by Sigmund Freud and Abraham Maslow to find out the problem dealing with the psychological conflicts h appened. The sources of the data in this study are divided into two categories; the primary source and the secondary source. The primary source is the novel of The Kite Runner and the secondary source is the supporting data from textbook, journal, articles, and internet. The data are taken from the novel were the quotations showing psychological conflicts faced by the main character in the novel. Then, the secondary data were the interpreting, analyzing, commentary discussion of the primary source. The data were collected by means of reading and identifying data.